Investigation of the number of injector holes and injection angles for improved engine performance and emissions with hydrogen and gasoline fuel blends - Javad Zareei; John William Grimaldo Guerrero; KDV Prasad; Shirin Shomurotova; José R. Nuñez-Alvarez; Grether Lucía Real-Pérez; Enrique M. Barreno-Avila (Next Research, 2026)

Ask the audience: Characterization of diving pressure on marine caves using diving operators’ knowledge - CARLA QUILES-PONS; FRANCESCO MARESCA; NURIA R. DE LA BALLINA; ENRIC REAL; IGNACIO BAENA-VEGA; ANABEL MUÑOZ MUÑOZ; MERCÈ MORATÓ; SUSANA DÍEZ; SANDRA MALLOL; DAVID DÍAZ (Mediterranean Marine Science, 2025)
Marine caves are considered biodiversity hotspots and serve as refuge habitats for both endemic and non-endemic species. Due to their low resilience, this habitat is considered vulnerable and is included as a key habitat in the European Union’s (EU) Habitats Directive (92/43/EEC). Recreational diving has been identified as a significant threat to this habitat, causing sediment resuspension, destruction of epibenthic organisms by contact, and the accumulation of exhaled air from divers on the ceiling, which can lead to the death of benthic organisms trapped in the air pockets. Consequently, urgent management measures for recreational diving in this fragile habitat are necessary, particularly since this activity has experienced substantial growth during the last decades, evolving into a form of mass tourism. The development of effective management strategies for marine caves is challenging, astheir exploitation and distribution are poorly known and cannot be estimated using traditional oceanographic mapping techniques applied to other benthic habitats. In this study, we conducted face-to-face, semi-structured questionnaires with dive operators, and used their Local Ecological Knowledge to estimate the spatial distribution of submerged and semi-submerged marine caves affected by recreational diving, the frequency of this activity, and the perception of diving centers regarding the impact of their activity on marine caves of the islands of Majorca and Menorca (Balearic Islands, Spain). Additionally, diving centers were asked to suggest potential measures to mitigate these impacts. Our results indicate that this approach is effective in identifying marine caves affected by recreational diving (a total of 111 marine caves were identified) and in determining key factors regarding the impact of recreational diving (accessibility of the cave and proximity to the diving center). This methodology also reveals that dive operators are generally aware of the reasons for protecting marine caves and the good practices required to protect this habitat, but little effort is made to implement these practices. These findings underline priority areas for intervention and suggest conservation practices to manage recreational diving in marine caves.

Interconnected robotic platforms inform deep-sea ecological restoration trends - Ivan Masmitja; Narcís Palomeras; Daniel M. Toma; Nixon Bahamon; Matias Carandell; José A. García del Arco; Damianos Chatzievangelou; Marta Real; Antoni Sánchez-Márquez; Gerard Batet; Pau Vial; Francisco Bonin-Font; et al. (Marine Pollution Bulletin, 2025)

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Increased serologic reactivity with automated CMIA testing and its implications for deceased donor eligibility determination in the United States - Sara O. Dionne; Hillary C. S. R. Akana; Michael Real; Kimberly A. Elliott; Brenden R. O’Neale (Cell and Tissue Banking, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Skeletal muscle alterations in Marfan syndrome: a systematic review - Audrei R. Santos; Rita M. S. Gutierrez; Tatiana E. Koike; Talita C. Conte; Caroline C. Real; Nicolas A. Dumont; Elen H. Miyabara (Journal of Muscle Research and Cell Motility, 2025)

Signs of northward expansion of the fireworm Hermodice carunculata in the Spanish Western Mediterranean Sea - NURIA R. DE LA BALLINA; FRANCESCO MARESCA; ENRIC REAL; IGNACIO BAENA-VEGA; SUSANA DÍEZ; ALEJANDRO MARTÍN-ARJONA; SANDRA MALLOL; DAVID DÍAZ (Mediterranean Marine Science, 2025)
The bearded fireworm Hermodice carunculata is a thermophilic polychaeta typically inhabiting the warmer waters of the Atlantic Ocean and the southern Mediterranean Sea. Over the past few years, sightings of this species have become more frequent at higher latitudes along the western Mediterranean (WM) basin, raising concerns about the potential expansion of its distribution range. Here, we present new records of H. carunculata obtained from the combination of benthos monitoring programmes, local ecological knowledge, and publicly available information. Furthermore, we investigated whether a northward shift in H. carunculata distribution has occurred, based on a temporal comparison of occurrence records before and after the record-breaking marine heat wave of 2022 2023. The present study improves the picture of the geographical distribution of this polychaete in the WM: we report a total of 257 new records of H. carunculata along the Mediterranean Spanish coast. The spatial and temporal distribution of these records suggests a northward expansion of the species, according to all data sources. The mean latitude of observations increased by nearly one degree, and the northernmost sightings extended up to 2.2° beyond the previously reported limits. These findings indicate the possible expansion of H. carunculata distribution in the Spanish WM and highlight the effectiveness of combining traditional monitoring methods and local ecological knowledge for detecting changes in species distribution.

Neuroimaging and immunofluorescence of the Pseudopus apodus brain: unraveling its structural complexity - S. Jiménez; R. Morona; M. J. Ruiz-Fernández; E. Fernández-Valle; D. Castejón; M. I. García-Real; J. González-Soriano; N. Moreno (Brain Structure and Function, 2025)
The present study provides an in-depth neuroanatomical characterization of the brain of Pseudopus apodus , combining magnetic resonance imaging (MRI) with histological analysis by immunofluorescence. In the telencephalon, the pallial regions showed distinct anatomical features, including a cortical structure, a dorsal ventricular ridge and the spherical nucleus, but prominent layering patterns, observable on histological slides, were not fully resolved by MRI. Subpallial structures, such as the nucleus accumbens and the basal ganglia, were delineated with histological clarity and further supported by MRI. In the hypothalamic and diencephalic regions, the dense and complex cellular composition made precise delineation of individual nuclei difficult by MRI, in contrast to the histological accuracy, however by MRI the identification of the major tracts running through these domains are clearly identifiable. Mesencephalic and rhombencephalic structures, including the optic tectum, isthmic nuclei, cerebellum, and reticular groups, were systematically described using a combination of histological and MRI techniques. In addition, immunofluorescence analysis of specific markers, such as Calretinin, ChAT, Isl1, Satb1, Serotonin and Tyrosine Hydroxylase, provided higher resolution of functional sub-regions, allowing precise identification of boundaries and facilitating comprehensive regional mapping, showing complex organizational arrangements, both in rostral regions, such as the dorsal ventricular crest, and in caudal regions, within the tegmental and posterior nuclei of the brain, including the ventral tegmental area, substantia nigra and raphe nuclei. These findings establish a robust neuroanatomical framework for Pseudopus apodus , contributing significantly to the understanding of reptile brain organization and providing valuable insights into the evolutionary adaptations underlying a limbless lizard neuroanatomy.

The neurotoxicity of pesticides: Implications for Parkinson's disease - Leslie Amaral; Márcia Martins; Manuela Côrte-Real; Tiago F. Outeiro; Susana R. Chaves; António Rego (Chemosphere, 2025)

A versatile yeast model identifies the pesticides cymoxanil and metalaxyl as risk factors for synucleinopathies - Leslie Amaral; Filipa Mendes; Manuela Côrte-Real; António Rego; Tiago F. Outeiro; Susana R. Chaves (Chemosphere, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Evaluation of the sorption/desorption processes of pesticides in biodegradable mulch films used in agriculture - Harshit Sahai; María Dolores Hernando; María Jesús Martínez Bueno; Ana M. Aguilera del Real; Amadeo R. Fernández- Alba (Chemosphere, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Increased ATP Release and Higher Impact of Adenosine A2A Receptors on Corticostriatal Plasticity in a Rat Model of Presymptomatic Parkinson’s Disease - Francisco Q. Gonçalves; Filipe C. Matheus; Henrique B. Silva; Joana I. Real; Daniel Rial; Ricardo J. Rodrigues; Jean-Pierre Oses; António C. Silva; Nélio Gonçalves; Rui D. Prediger; Ângelo R. Tomé; Rodrigo A. Cunha (Molecular Neurobiology, 2023)
Extracellular ATP can be a danger signal, but its role in striatal circuits afflicted in Parkinson’s disease (PD) is unclear and was now investigated. ATP was particularly released at high stimulation intensities from purified striatal nerve terminals of mice, which were endowed with different ATP-P2 receptors (P2R), although P2R antagonists did not alter corticostriatal transmission or plasticity. Instead, ATP was extracellularly catabolized into adenosine through CD73 to activate adenosine A 2A receptors (A 2A R) modulating corticostriatal long-term potentiation (LTP) in mice. In the presymptomatic phase of a 6-hydroxydopamine rat model of PD, ATP release from striatal nerve terminals was increased and was responsible for a greater impact of CD73 and A 2A R on corticostriatal LTP. These observations identify increased ATP release and ATP-derived formation of extracellular adenosine bolstering A 2A R activation as a key pathway responsible for abnormal synaptic plasticity in circuits involved in the onset of PD motor symptoms. The translation of these findings to humans prompts extending the use of A 2A R antagonists from only co-adjuvants of motor control in Parkinsonian patients to neuroprotective drugs delaying the onset of motor symptoms.

Acetic acid triggers cytochrome c release in yeast heterologously expressing human Bax - Joana P. Guedes; Vitória Baptista; Cátia Santos-Pereira; Maria João Sousa; Stéphen Manon; Susana R. Chaves; Manuela Côrte-Real (Apoptosis, 2022)

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Evaluation of gully development over several years using GIS and fractal analysis: a case study of the Palmital watershed, Minas Gerais (Brazil) - L. S. C. Real; S. Crestana; R. R. M. Ferreira; V. G. S. Rodrigues (Environmental Monitoring and Assessment, 2020)

Brain alterations in low-frequency fluctuations across multiple bands in obsessive compulsive disorder - Mònica Giménez; Andrés Guinea-Izquierdo; Victoria Villalta-Gil; Ignacio Martínez-Zalacaín; Cinto Segalàs; Marta Subirà; Eva Real; Jesús Pujol; Ben J Harrison; Josep Maria Haro; Joao R Sato; Marcelo Q Hoexter; et al. (Brain Imaging and Behavior, 2017)

Treadmill Exercise Prevents Increase of Neuroinflammation Markers Involved in the Dopaminergic Damage of the 6-OHDA Parkinson’s Disease Model - Caroline Cristiano Real; Priscila Crespo Garcia; Luiz R. G. Britto (Journal of Molecular Neuroscience, 2017)

A porcine circovirus-2 mutant isolated in Brazil contains low-frequency substitutions in regions of immunoprotective epitopes in the capsid protein - Rafael Locatelli Salgado; Pedro Marcus Pereira Vidigal; Natalia F. Gonzaga; Luiz F. L. de Souza; Marcelo D. Polêto; Thiago Souza Onofre; Monique R. Eller; Carlos Eduardo Real Pereira; Juliana L. R. Fietto; Gustavo C. Bressan; Roberto M. C. Guedes; Márcia R. Almeida; et al. (Archives of Virology, 2015)

NGS metabarcoding proves successful for quantitative assessment of symbiont abundance: the case of feather mites on birds - J. Diaz-Real; D. Serrano; A. Piriz; R. Jovani (Experimental and Applied Acarology, 2015)

Assessment of hormone-like activities in Ginkgo biloba , Elettaria cardamomum and Plantago ovata extracts using in vitro receptor-specific bioassays - Macarena Real; José-Manuel Molina-Molina; Jesús Jimenez; Horacio R. Diéguez; Mariana F. Fernández; Nicolás Olea (Food Additives & Contaminants: Part A, 2015)

Quality and Safety Requirements for Sustainable Phage Therapy Products - Jean-Paul Pirnay; Bob G. Blasdel; Laurent Bretaudeau; Angus Buckling; Nina Chanishvili; Jason R. Clark; Sofia Corte-Real; Laurent Debarbieux; Alain Dublanchet; Daniel De Vos; Jérôme Gabard; Miguel Garcia; et al. (Pharmaceutical Research, 2015)

Core amino acid variation at position 110 is associated with sustained virological response in Caucasian patients with chronic hepatitis C virus 1b infection - F. A. Di Lello; J. A. Mira; K. Neukam; M. Parra-Sánchez; J. R. Guelfo; C. Cifuentes; J. Macías; J. C. Palomares; J. Gómez-Mateos; J. A. Pineda; Luis M. Real (Archives of Virology, 2014)

Novel in vitro systems for prediction of veterinary drug residues in ovine milk and dairy products - L. González-Lobato; R. Real; D. Herrero; A. de la Fuente; J.G. Prieto; M.M. Marqués; A.I. Álvarez; G. Merino (Food Additives & Contaminants: Part A, 2014)

Biochemical and structural studies on native and recombinant Glycine max UreG: a detailed characterization of a plant urease accessory protein - Rafael Real-Guerra; Fernanda Staniscuaski; Barbara Zambelli; Francesco Musiani; Stefano Ciurli; Célia R. Carlini (Plant Molecular Biology, 2012)

Prioritisation of novel pasture species for use in water-limited agriculture: a case study of Cullen in the Western Australian wheatbelt - R. G. Bennett; M. H. Ryan; T. D. Colmer; D. Real (Genetic Resources and Crop Evolution, 2011)

A new approach for determination of Na,K-ATPase activity: application to intact pancreatic β-cells - Ana R. Costa; Joana Real; Célia M. Antunes; Júlio Cruz-Morais (In Vitro Cellular & Developmental Biology - Animal, 2010)

Determination of the optimal size of area to be sampled by use of the moss biomonitoring technique - Zulema Varela; J. A. Fernández; J. R. Aboal; C. Real; A. Carballeira (Journal of Atmospheric Chemistry, 2010)

What is the impact of wind farms on birds? A case study in southern Spain - M. A. Farfán; J. M. Vargas; J. Duarte; R. Real (Biodiversity and Conservation, 2009)

Temperature influences the expression of fimbriae and flagella in Hafnia alvei strains: an immunofluorescence study - D. Padilla; F. Acosta; J. A. García; F. Real; Jose R. Vivas (Archives of Microbiology, 2009)

Modelling the impact of climate extremes: an overview of the MICE project - C. E. Hanson; J. P. Palutikof; M. T. J. Livermore; L. Barring; M. Bindi; J. Corte-Real; R. Durao; C. Giannakopoulos; P. Good; T. Holt; Z. Kundzewicz; G. C. Leckebusch; et al. (Climatic Change, 2007)

Land use and environmental factors affecting red-legged partridge (Alectoris rufa) hunting yields in southern Spain - J. M. Vargas; J. C. Guerrero; M. A. Farfán; A. M. Barbosa; R. Real (European Journal of Wildlife Research, 2006)

Relative importance of environment, human activity and spatial situation in determining the distribution of terrestrial mammal diversity in Argentina - Raimundo Real; A. Márcia Barbosa; Daniela Porras; Marta S. Kin; Ana L. Márquez; José C. Guerrero; L. Javier Palomo; Enrique R. Justo; J. Mario Vargas (Journal of Biogeography, 2003)
Aim The partition of the geographical variation in Argentinian terrestrial mammal species richness (SR) into environmentally, human and spatially induced variation. Location Argentina, using the twenty‐three administrative provinces as the geographical units. Methods We recorded the number of terrestrial mammal species in each Argentinian province, and the number of species belonging to particular groups (Marsupialia, Placentaria, and among the latter, Xenarthra, Carnivora, Ungulates and Rodentia). We performed multiple regressions of each group's SR on environmental, human and spatial variables, to determine the amounts of variation explained by these factors. We then used a variance partitioning procedure to specify which proportion of the variation in SR is explained by each of the three factors exclusively and which proportions are attributable to interactions between factors. Results For marsupials, human activity explains the greatest part of the variation in SR. The purely environmental and purely human influences on all mammal SR explain a similarly high proportion of the variation in SR, whereas the purely spatial influence accounts for a smaller proportion of it. The exclusive interaction between human activity and space is negative in carnivores and rodents. For rodents, the interaction between environment and spatial situation is also negative. In the remaining placental groups, pure spatial autocorrelation explains a small proportion of the variation in SR. Main conclusions Environmental factors explain most of the variation in placental SR, while Marsupials seem to be mainly affected by human activity. However, for edentates, carnivores, and ungulates the pure human influence is more important than the pure spatial and environmental influences. Besides, human activity disrupts the spatial structure caused by the history and population dynamics of rodents and, to a lesser extent, of carnivores. The historical events and population dynamics on the one hand, and the environment on the other, cause rodent SR to vary in divergent directions. In the remaining placental groups the autocorrelation in SR is mainly the result of autocorrelation in the environmental and human variables.